From Governance to Action: The Mediating Role of Operational Practices in Achieving Sustainable Development Goals in Higher Education (Architecture Image Studies, 2025)
This study explains the causal mechanism linking Risk Management Practices (RMP) to specific Sustainable Development Goal (SDG) outcomes within higher education. Using PLS-SEM on a survey of 210 Thai administrators, we test a new mediation model. The findings indicate that strategic "drivers" (Risk Governance & Strategy) have no direct impact on sustainability. Instead, their influence is fully mediated by operational "mechanisms" (Risk Performance & Monitoring). These mechanisms are the significant direct predictors for both Operational & Environmental outcomes (related to SDG 7, 9, 11, & 12) and Social & People outcomes (related to SDG 3, 5, & 8). This study provides a new process model, proving that strategy must be translated into operational action to achieve tangible sustainability results.